A direct method for dissipative dynamical systems by using the symplectic Brezis‐Ekeland‐Nayroles principle. Issue 1 (17th December 2018) - Nguyen, An Danh; Markert, Bernd
Abstract: We study a direct method for inelastic structures by using the symplectic Brezis‐Ekeland‐Nayroles variational principle, which provides a minimum regulation for whole trajectories. The null minimisation problem of the power balance is established and discretised by the use of the orthogonal collocation method. The proposed approach is illustrated with an example of a thick tube subjected to internal loadings. Numerical results are presented and compared with the analytical solutions.